Exploration of novel therapeutics for autosomal dominant Retinitis Pigmentosa - Cronin, Thérèse (Trinity College (Dublin, Ireland). Department of Genetics, 2006)
This thesis is concerned with exploration of a suppression and replacement therapeutic approach for the dominant form of Retinitis Pigmentosa (ADRP). Retinitis Pigmentosa is the most heterogeneous of all hereditary disorders and as such presents special challenges as a disease model for intervention by m olecular therapies. The main focus of this thesis has centred on the gene encoding the opsin pigment, rhodopsin - the source of many ADRP-causing mutations. Essentially siRNA-expressing vectors have been employed to downregulate transcript levels from this gene, and the effect has been assessed in transformed cell lines as well as in a retinal cell culture model.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin